Experimental investigation of Kevlar/carbon/glass/polyurethane foam epoxy hybrid sandwich composites with nano silicon particles in low-velocity impact events - Mani, Megavannan; Thiyagu, M.; Kumar Krishnan, Pradeep (Materials today : proceedings, 2023)
•Hand layup method is used to develop hybrid sandwich composite.•Silica nanoparticles 2 wt%, and 4 wt%.•Stacking sequence (01 K/01C/01G/PUR/01G/01C/01 K) was maintained.•Tensile strength of 24.2%, shear strength of 23.81% significantly improved.•Torsional strength 12.54% improved compared with base material. Hybrid sandwich polymer structures are employed in various secondary aerospace applications like antennas, solar panels, tailplanes, wings, doors, and control structures owing to their wide range of advantages. The present investigation explored the better functionality of sandwich polymer panels' impact strengths during barely visible low-velocity impact (LVI) analysis. These constructions are built of polyurethane (PUR) foam materials with kevlar, carbon, glass, and epoxy polymer structures. The silica nanoparticles were added at weight percentages of 0, 2, and 4. As a result, enhanced hybrid sandwich polymer panels were developed. The hand layup method is used to develop hybrid sandwich composite structures with silica nanoparticles. The stacking sequence method was used to stack these laminate structures as per ASTM standards (01K/01C/01G/PUR/01G/01C/01K), and the combination of these composite panels with wt. 4% silicon nanoparticles (SiNPs) fillers exhibits 24.2% higher tensile strength, 23.81% improved shear strength, and 12.54% higher torsional strength compared to those without silica nanoparticle’s composite structure. The combination of 2 wt% of SNiPs inclusion in sandwich composite structures improved tensile, shear, and torsional strength by 16.27%, 12.89%, and 7.41%, respectively, when compared with that of wt. 0% of SNiPs added to sandwich composite structures.